Ethics of Artificial Intelligence: Case Studies and Options for Addressing Ethical Challenge (excerpt) - Bernd Stahl; Doris Schroeder; Rowena Rodrigues (Journal of Economic Sociology, 2024)
Ethics of Artificial Intelligence: Case Studies and Options for Addressing Ethical Challenges is based on the work that Prof. B. C. Stahl, Prof. D. Schroeder and R. Rodrigues were engaged in within the framework in a number of different projects. The main project that brought the authors together and demonstrated the need for case studies addressing ethical AI problems and ways to solve them was the EU-funded Shaping the Ethical Dimensions of Smart Information System (SHERPA; 2018–2021). This book provides real-life examples of ethical issues, along with discussions and coping strategies. The book is based on the case study method. Case studies are one of the best ways to learn about ethical dilemmas and gain insights into the various complexities and perspectives of stakeholders. The Journal of Economic Sociology publishes the first chapter of the book “Ethics of Artificial Intelligence: An Introduction”, where the authors present their problem statement and outline the structure of their book.